2013
DOI: 10.1051/0004-6361/201220939
|View full text |Cite
|
Sign up to set email alerts
|

Competition of rotation and stratification in flux concentrations

Abstract: Context. In a strongly stratified turbulent layer, a uniform horizontal magnetic field can become unstable and spontaneously form local flux concentrations due to a negative contribution of turbulence to the large-scale (mean-field) magnetic pressure. This mechanism, which is called negative effective magnetic pressure instability (NEMPI), is of interest in connection with dynamo scenarios in which most of the magnetic field resides in the bulk of the convection zone and not at the bottom, as is often assumed.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 20 publications
(62 citation statements)
references
References 43 publications
6
55
1
Order By: Relevance
“…We begin by reproducing some of the DNS results of Losada et al (2013), who found the suppression of the growth rate of NEMPI with increasing values of Co and a subsequent enhancement at larger values, which they interpreted as being the result of dynamo action in the presence of an externally applied magnetic field. We also use DNS to determine independently the expected efficiency of the dynamo by estimating the α effect from kinetic helicity measurements and by computing both α effect and turbulent diffusivity directly using the test-field method (TFM).…”
Section: Dns Studymentioning
confidence: 81%
See 2 more Smart Citations
“…We begin by reproducing some of the DNS results of Losada et al (2013), who found the suppression of the growth rate of NEMPI with increasing values of Co and a subsequent enhancement at larger values, which they interpreted as being the result of dynamo action in the presence of an externally applied magnetic field. We also use DNS to determine independently the expected efficiency of the dynamo by estimating the α effect from kinetic helicity measurements and by computing both α effect and turbulent diffusivity directly using the test-field method (TFM).…”
Section: Dns Studymentioning
confidence: 81%
“…In studying this process in detail, we have a chance of detecting new joint effects resulting from the two instabilities, which is one of the goals of the present paper. However, these two instabilities may also compete against each other, as was already noted by Losada et al (2013). The large-scale dynamo effect relies on the combined presence of rotation and stratification, while NEMPI requires stratification and large enough scale separation.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Our present study therefore supports ideas about a shallow origin for active regions and sunspots (Brandenburg 2005;Brandenburg et al 2010;Kitiashvili et al 2010;Stein & Nordlund 2012), contrary to common thinking that sunspots form near the bottom of the convective zone (Parker 1975;Spiegel & Weiss 1980;D'Silva & Choudhuri 1993). More specifically, the studies of Losada et al (2013) point toward the possibility that magnetic flux concentrations form in the top 6 Mm, i.e., in the upper part of the supergranulation layer.…”
Section: Discussionmentioning
confidence: 99%
“…A more physical alternative is to use only nonhelical forcing, but to include rotation to produce helicity in conjunction with the stratification. Such models have recently been considered by Losada et al (2013), who found that NEMPI begins to be suppressed by rotation at Coriolis numbers somewhat below those where α 2 -type dynamo action sets in. Furthermore, there is now evidence that the combined action of NEMPI and the dynamo instability has a lower threshold than the dynamo alone.…”
Section: Discussionmentioning
confidence: 99%